Performance Comparision of Internal and External Rotor Structured Wind Generators Mounted from Same Permanent Magnets on Same Geometry - Tarımer, İ. and Ocak, C. (Elektronika ir Elektrotechnika, 2009)
In this study, internal and external rotor radial-flux machine constructions built with surface mounted by applying the same NdFeB were compared according to torque density, vigorous material weight, outer radius, total length and volume, generated power and efficiency. Induced phase voltages and winding currents under load, airgap flux density, output power versus speed and material consumption for internal and external rotor PM generators have been obtained as the results of comparison. It was inferred that external rotor PM machines have a smaller volume, lower output power and efficiency, higher armature thermal load and current density than internal rotor PM machines by applying the same PM geometry and features for a given power rating. Therefore it was seen that the external rotor construction was more suitable to be applied in wind power systems because of external rotor structured PM machines have lower total weight and cost. Ill. 12, bibl. 12 (in English; summaries in English, Russian and Lithuanian).